2019
DOI: 10.1097/mph.0000000000001556
|View full text |Cite
|
Sign up to set email alerts
|

Gram-negative Bacteremia in Children With Hematologic Malignancies and Following Hematopoietic Stem Cell Transplantation: Epidemiology, Resistance, and Outcome

Abstract: Gram-negative rod (GNR) infections adversely affect the outcome of patients with malignancies and following hematopoietic stem cell transplantation (HSCT). This retrospective observational study aimed to describe the epidemiology, outcome, and resistance patterns of GNR bacteremia in children with hematologic malignancies (HM) and after HSCT during the period spanning from 2010 to 2014 in a tertiary children’s hospital. A total of 270 children were included in the analysis; 65 (24%) developed 85 episodes of GN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 23 publications
3
20
1
Order By: Relevance
“…With this system, hands-on time from PBC bottles is < 2 minutes (19). The panel was challenged with a well-populated sample set representing the most identified gram-negative bloodstream pathogens (20)(21)(22)(23)(24)(25) and ARG targets, with an overall accuracy of 92.9% after discordant resolution. Although molecular discordant resolution has limitations, it is a practical option for a comparative accuracy study for molecular multiplex methods as conventional culture methods cannot detect nucleic acid and therefore Downloaded from https://journals.asm.org/journal/jcm on 13 July 2021 by 44.224.250.200. cannot verify the presence or absence of genetic sequences.…”
Section: Discussionmentioning
confidence: 99%
“…With this system, hands-on time from PBC bottles is < 2 minutes (19). The panel was challenged with a well-populated sample set representing the most identified gram-negative bloodstream pathogens (20)(21)(22)(23)(24)(25) and ARG targets, with an overall accuracy of 92.9% after discordant resolution. Although molecular discordant resolution has limitations, it is a practical option for a comparative accuracy study for molecular multiplex methods as conventional culture methods cannot detect nucleic acid and therefore Downloaded from https://journals.asm.org/journal/jcm on 13 July 2021 by 44.224.250.200. cannot verify the presence or absence of genetic sequences.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in pediatric patients with hematologic malignancies showed that prolonged neutropenia and duration of hospitalization were associated with Gram-negative infection, especially carbapenem-resistant bacteremia. 15 In our study, 81% of FN patients were diagnosed with acute leukemia and 98 (39.7%) underwent stem-cell transplantation. The reason for these data may be that patients who underwent stemcell transplantation or induction and consolidation for acute leukemia were prescribed higher-dose chemotherapy, which may cause longer neutropenia.…”
Section: Discussionmentioning
confidence: 60%
“…10 In a 2019 study of 126 children with malignant bone tumors, the only infectionrelated mortality occurred in children with severe neutropenia. 7 Although not all infections and deaths in these studies occurred in a critical care environment, the strong association between severe neutropenia and these adverse outcomes warrants inclusion of severe neutropenia in these criteria.…”
Section: Severe Neutropeniamentioning
confidence: 97%
“…Data from the oncology literature has long indicated that an absolute neutrophil count ([% neutrophils 1 % band forms] × total white blood cell count) <500 cells per mm 3 confers significantly increased risk for the development of new infection and death. [7][8][9][10][11] A 10-year single-center survey of patients receiving cytolytic chemotherapy revealed that persistent neutropenia was strongly associated with mortality. 9 In a recent study of 270 children after hematopoietic stem cell transplant, prolonged severe neutropenia (>7 days) was strongly associated with an increased risk for Gram-negative bacteremia (odds ratio 19.5, 95% confidence interval 2.6-148).…”
Section: Severe Neutropeniamentioning
confidence: 99%
See 1 more Smart Citation